Normalized Study of Three-Parameter System in the Time Domain and Frequency Domain - Xiao-Lei Jiao; Yang Zhao; Wen-Lai Ma (Shock and Vibration)
Three-parameter isolation system can be used to isolate microvibration for control moment gyroscopes. Normalized analytical model for three-parameter system in the time domain and frequency domain is proposed by using analytical method. Dynamic behavior of three-parameter system in the time domain and frequency domain is studied. Response in the time domain under different types of excitations is analyzed. In this paper, a regulatory factor is defined in order to analyze dynamic behavior in the frequency domain. For harmonic excitation, a comparison study is made on isolation performance between the case when the system has optimal damping and the case when regulatory factor is 1. Besides, phase margin of three-parameter system is obtained. Results show that dynamic behavior in the time domain and frequency domain changes with regulatory factor. Phase margin has the largest value when the value of regulatory factor is 1. System under impulse excitation and step excitation has the shortest settling time for the response in the time domain when the value of regulatory factor is 1. When stiffness ratio is small, isolation performances of two cases are nearly the same; when system has a large stiffness ratio, isolation performance of the first case is better.